Oceanographic Data of the 47th Japanese Antarctic Research Expedition from December 2005 to March 2006 - マスダ, タカヒロ; イトウ, ヨシノブ; Masuda, Takahiro; Ito, Yoshinobu (National Institute of Polar Research, 2008)
P(論文) departmental bulletin paper